Changes of masseter muscle after mandible distraction osteogenesis in patients with Hemifacial microsomia: a retrospective study - Han, Wenqing; Kim, Byeong Seop; Zhang, Ziwei; Chen, Xiaojun; Yan, Yingjie; Lin, Li; Zhang, Yan; Chai, Gang (Frontiers in Pediatrics, 2024)
Mandible distraction osteogenesis (MDO) is widely used to reconstruct the mandible in patients with mild Hemifacial microsomia (HFM). However, the masseter's response to mandible distraction remains unclear. In this study, we analyze the effect of the surgical intervention on masseter muscle by a retrospective analysis. A retrospective analysis involved 21 HFM patients who underwent mandible distraction osteogenesis from 2015 to 2020. The procedure consisted of a five-day latent period, a three-week distraction period, and a six-month consolidation period. CT data were manually segmented and measured with Mimics software before surgery, within 3 months, and more than 1 year postoperatively. Masseter volume, masseter length, masseter width, and mandible ramus height were measured and analyzed using paired t-test, Pearson, and Spearman correlation analysis. We included 21 patients with HFM who underwent mandible distraction osteogenesis from 2015 to 2020. The masseter volume on the affected side increased immediately after surgery from (6505.33±3671.95) mm 3 to (10194.60±5638.79) mm 3 , but decreased to (8148.38±3472.57) mm 3 at the second follow-up correlated to mandible ramus height (r=0.395, P=0.038). A similar trend was observed in changes in masseter length. Symmetry and width of masseter muscle had no longitudinal statistical significance. Masseter muscle involvement benefits from MDO in the short term. To achieve long-term efficacy, more attention should be paid to muscle reconstruction.